A pilot study on the global practice of informed consent in paediatric dentistry - Potgieter, Nicoline; Bridge, Gemma; Elfrink, Marlies; Folayan, Morenike Oluwatoyin; Gao, Sherry S.; Groisman, Sonia; Jawdekar, Ashwin; Kemoli, Arthur M.; Lim, David; Ly, Phuong; Mani, Shani A.; Masumo, Ray; et al. (Frontiers in Oral Health, 2024)
Background Conducting oral treatment early in the disease course, is encouraged for better health outcomes. Obtaining informed consent is an essential part of medical practice, protecting the legal rights of patients and guiding the ethical practice of medicine. In practice, consent means different things in different contexts. Silver Diamine Fluoride (SDF) and Silver Fluoride (SF) is becoming popular and cost effective methods to manage carious lesions, however, cause black discolouration of lesions treated. Obtaining informed consent and assent is crucial for any dental treatment—and has specific relevance with SDF/ SF treatments. Methods The aim of this paper is to describe informed consent regulations for dental care in a selection of countries, focusing on children and patients with special health care needs. An online survey was shared with a convenience sample of dental professionals from 13 countries. The information was explored and the processes of consent were compared. Results Findings suggest that there are variations in terms of informed consent for medical practice. In Tanzania, South Africa, India, Kenya, Malaysia and Brazil age is the determining factor for competence and the ability to give self-consent. In other countries, other factors are considered alongside age. For example, in Singapore, the United Kingdom, and the United States the principle of Gillick Competence is applied. Many countries' laws and regulations do not specify when a dentist may overrule general consent to act in the “best interest” of the patient. Conclusion It is recommended that it is clarified globally when a dentist may act in the “best interest” of the patient, and that guidance is produced to indicate what constitutes a dental emergency. The insights gathered provide insights on international practice of obtaining informed consent and to identify areas for change, to more efficient and ethical treatment for children and patients with special needs. A larger follow up study is recommended to include more or all countries.